HearCARE: Hearing and Communication Assistance for Resident Engagement - Palmer, Catherine V.; Mulla, Reem; Dervin, Elizabeth; Coyan, Kathleen Costigan (Seminars in Hearing, 2017)
Impaired hearing is related to poor health outcomes, including compromised cognitive function, in aging individuals. Hearing loss is the third most common chronic health condition after arthritis and heart disease in older adults and the fourth most detrimental condition related to quality of life in older adults. Only 18% of aging adults who have impactful hearing loss actually use custom-fit amplification. Therefore, the majority of aging individuals entering senior living facilities will have untreated hearing loss. Older adults move to senior communities to maintain or increase their social engagement, to receive care from qualified staff, and to ultimately enhance their quality of life. We know that the majority of individuals over 65 years of age have significant hearing loss, which leaves them with complex listening needs due to low incidence of hearing aid use, group communication situations that are common for social activities, interactive dining environments, and the need for telephone use to connect with loved ones. Busy staff and family members may not be aware of the impact of decreased hearing on quality of life, as well as caregiver burden. HearCARE (Hearing and Communication Assistance for Resident Engagement) is an initiative to provide communication assistance on a day-to-day basis in senior living facilities in a cost-effective manner. This innovative model for delivering audiology services and communication assistance in senior living communities employing communication facilitators who are trained and supervised by an audiologist will be described. Data related to the communication facilitator training, daily activities, interactions with the audiologist, use of devices, and impact on residents, staff, and families will be described.
Keywords: Aging; untreated hearing loss; cognition